George Frankl: an undervalued voice in the history of autism - Muratori, Filippo; Calderoni, Sara; Bizzari, Valeria (European child & adolescent psychiatry, 2021)
This paper aims to propose that the psychiatrist George Frankl had more than a marginal role in the early history of autism. Frankl’s conception of autism as characterized by a lack of affective language has influenced both Asperger and Kanner. First, this proposal is historically supported; second it is corroborated by Frankl’s unpublished manuscript on Autism. We found that Frankl’s perspective about autism was, and still can be, considered innovative for multiple reasons. Specifically, Frankl proposed that autism could cover a spectrum of conditions; that it is a state of mind that is not necessarily abnormal; and that it is a neurobiological condition, which primarily needs to be understood by others. Finally, Frankl’s concepts of affective contact and affective language are reconsidered with reference to contemporary neuropsychology from which autism emerges not as a higher-order cognitive deficit, but as a result of an impairment of primordial ability to process low level sensory, motor and perceptual information gained through experiencing other persons.
Online publiziert: 27. August 2020
Gesehen am 02.03.2026